Spiritual Emotional Freedom Technique (SEFT) Sebagai Metode Terapi Sufistik - Farmawati, Cintami (Madaniyah, 2018)
This research aims to know the application of Spiritual Emotional Freedom Technique (SEFT) as method of sufistic therapy in overcoming mental disorders in Rumah Perlindungan Sosial Berbasis Masyarakat (RPSBM) Pekalongan City. This research is a qualitative with case study approach. The population of this study is all patient of mental disorder, with sample 4 patient of mental disorder, taken by purposive sampling. Data collecting in research using library study and field study. Analysis of data using data reduction, data publishing and conclusion. The result showed that SEFT is a combination of spiritual power and energy psychology, of which 90% emphasizes spirituality. With SEFT, the subject is brought to the belief that healing comes from God so that it can be sincere and resigned to the mental problems that it undergoes.Â Keywords: mental disorders, SEFT, sufistic therapy